Aspiração de corpo estranho: causa de estridor recorrente no lactente - Relato de caso - Rafaela Baroni Aurilio; Carla Cristiane Dall Olio; Ana Alice Amaral Ibiapina Parente; Priscila Machado de Matos; Ana Flavia Costa Dalla Martha; Luzia Abraão El Hadj; Adriana Cristina da Luz Lopes (Residência Pediátrica)
Foreign body aspiration (FBA) is a common adverse event in pediatric practice, potentially fatal, that can present a variety of symptoms. Several factors contribute to the delay of diagnosis, promoting harm to the child and family. The diagnosis can be suggested by imaging exams and, most of the time, bronchoscopy is necessary. The present report will describe a case FBA in a young infant, highlighting the various confounding factors and possible mistakes during the investigation.